RACIAL RECRUITMENT IN POST-APARTHEID SOUTH AFRICA: DILEMMAS OF PRIVATE RECRUITMENT AGENCIES - Martin, Geraldine; Durrheim, Kevin (PINS-Psychology in Society, 2025)
This article examines the rhetoric of racial exclusion used by South African private recruitment consultants to justify racist practice and criticise employment equity legislation. Transcribed face-to-face interviews with nine consultants in two urban centres serve as textual evidence. These consultants engaged in a number of rhetorical manoeuvres to justify privileging whites for employment, including blaming their clients and constructing whiteness as normative and blackness as deficient. They provided ostensibly non-racial reasons for privileging whites. The analysis offers insight into the conservation of racial advantage in the context of radical socio-political change.